FACTOR ANALYSIS OF HOUSEHOLD SEWERAGE OWNERSHIP - Yuli Setiawati; Lilis Suryani; Arie Wahyudi; Maria Ulfah (Cendekia Medika: Jurnal Stikes Al-Ma`arif Baturaja, 2024)
Wastewater or sewage can have major and important effects on the environment and humans, especially resulting in pollution and infectious diseases. In general, households in Indonesia dispose of their waste directly into the sewer and without shelter.  This study aims to determine the factors associated with household SPAL ownership in the Trimoharjo Health Center Working Area. Quantitative research design with a cross-sectional approach. The sampling technique used purposive sampling. The sample obtained was 100 respondents. Data collection using questionnaires. Bivariate data analysis using chi-Square test and multivariate logistic regression.  The results showed that there was a relationship between knowledge (p value 0.000), the role of officers (p value 0.001) and the role of community leaders (p value 0.021) on household SPAL ownership. There was no relationship between attitude (p value 0.93), socioeconomic status (p value 0.06) and home ownership status (p value 1.00) towards household SPAL ownership. The most dominant factor with household SPAL ownership was knowledge (OR 0.026).  It can be concluded that there is a relationship between knowledge, the role of officials and the role of community leaders in household SPAL ownership